HUBUNGAN FAKTOR – FAKTOR RISIKO DENGAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT PADA BALITA DI DESA BANDA BARU KECAMATAN AMAHAI KABUPATEN MALUKU TENGAH TAHUN 2020 - Victoria Inri Imania Wattimena; Nathalie E Kailola; Josepina Mainase (PAMERI, 2021)
Acute respiratory infection (ARI) is one of the most common diseases affecting children, both in developed and developing countries. WHO (World Health Organization) in 2007 also said that around 13 million children under five worldwide die every year and most of these deaths are in developing countries such as in Asia and Africa. ARI is caused by various types of viruses and bacteria. The bacteria that cause it are from the genus Streptococcus, Staphylococcus, Pnemococcus, Hemophilus, Bordetella, and Korinebacterium. Viruses that cause are the Microvirus, Adenovirus, Coronavirus, Pikonaviru and Mikoplasma, Herpesvirus. ARI can also be transmitted through saliva, sneezing, respiratory air that contains germs in the form of bacteria and viruses which are inhaled into the respiratory tract and air pollutants such as PM10, CO, and so on. Aim. The purpose of this study was to determine the relationship between risk factors and the incidence of ARI in toddlers in Banda Baru Village, Amahai District, Central Maluku Regency in 2020. Methods. The research method used was a cross sectional approach. The sampling technique used was total sampling in which all populations were sampled on the condition that they met the inclusion criteria. Results. The data collected by 43 respondents using a questionnaire. The results obtained with a large percentage, namely the type of floor factor that still used semi-permanent was obtained (81.4%) and those suffering from ISPA were (53.5%). Another percentage is from the cooking fuel variable where respondents who still use wood for cooking are (46.5%) and those who suffer from ARI (34.9%). Conclusion. Banda Baru Village residents are expected to minimize the factors that affect ARI.